Experimental Investigation of Cavitation Bulk Nanobubbles Characteristics Effects of pH and Surface-Active Agents - Prakash, Ritesh (Langmuir : the ACS journal of surfaces and colloids, 2023)
Nanobubbles (NBs) have a widespread application in antimicrobial activity, wastewater treatment, and ecological restoration due to numerous peculiar characteristics, such as small diameter, long-term stability, and ability to produce hydroxyl radicals. Despite significant applications, only limited comprehensive investigations are available on the role of surfactants and pH in NBs characteristics. Therefore, this study examines the effects of different surfactants (i.e., anionic, cationic, and nonionic) and pH medium on bulk NB formation, diameter, concentration, bubble size distribution (BSD), ζ-potential, and stability. The effect of surfactant at concentrations above and below the critical micelle concentration was investigated. NBs were generated in deionized (DI) water using a piezoelectric transducer. The stability of NBs was assessed by tracking the variation in diameter and concentration over time. In a neutral medium, the diameter of NBs is smaller than in other surfactant or pH mediums. The diameter, concentration, BSD, and stability of NBs are strongly influenced by the ζ-potential rather than the solution medium. BSD curve shifts to a smaller bubble diameter when the magnitude of ζ-potential is high in any solution. In pure water, surfactant, and pH mediums, NBs have existed for a long time. NBs have a shorter life span in environments with a pH ≤ 3. Surfactant adsorption on the surface of NBs increases with increasing surfactant concentration up to a certain limit, beyond which it declines substantially. The Derjaguin-Landau-Verwey-Overbeek (DLVO) theory was used to interpret the NBs stability, resulting in a total potential energy barrier that is positive and greater than 45.55 kBT for 6 ≤ pH ≤ 11, whereas for pH < 6, the potential energy barrier essentially vanishes. Moreover, an effort has also been made to explicate the plausible prospect of ion distribution and its alignment surrounding NBs in cationic and anionic surfactants. This study will extend the in-depth investigation of NBs for industrial applications involving NBs